The Analysis Study of Surgical Approaches and Outcome in Living Donor Nephrectomy: A Comprehensive Systematic Review - Adzana Yasadhy Hangga Prasetyo; Yosie Yulanda Putra (International Medical Journal Corp. Ltd, 2024)
Background: The shortage of deceased donor kidneys has led to a significant increase in the use of living donor kidneys for transplantation. Since the first successful living donor nephrectomy in the 1950s, surgical techniques have advanced considerably, evolving from open donor nephrectomy (ODN) to more refined minimally invasive procedures. This systematic review aims to compare the various surgical techniques for living donor nephrectomy and their outcomes. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: LDN and other minimally invasive techniques, such as RDN and robot-assisted nephrectomy, offer advantages in recovery time and reduced complications. However, each method has unique strengths and considerations. The choice of approach should depend on donor anatomy, surgeon expertise, and institutional resources.